2019
DOI: 10.1186/s12889-019-6472-3
|View full text |Cite
|
Sign up to set email alerts
|

Rugby Fans in Training New Zealand (RUFIT-NZ): a pilot randomized controlled trial of a healthy lifestyle program for overweight men delivered through professional rugby clubs in New Zealand

Abstract: BackgroundHealthy lifestyle programs that are designed specifically to appeal to and support men to improve lifestyle behaviors and lose weight are needed. The Rugby Fans in Training-New Zealand (RUFIT-NZ) program is delivered by professional rugby clubs and inspired by the successful Football Fans In Training program (FFIT), a gender sensitized weight loss program for obese middle-aged men delivered by professional football clubs in Scotland. RUFIT-NZ required development and evaluation for feasibility.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(70 citation statements)
references
References 37 publications
2
68
0
Order By: Relevance
“…A −2.5 kg (95% CI −5.4 to 0.4) mean weight loss at 12 weeks favored the intervention group, who also showed positive improvements in waist circumference, resting heart rate, diastolic blood pressure, cardiovascular fitness and 'adherence' to lifestyle behaviors. All men who were followed up reported that they liked the program and would recommend it to other men [60]. As outcomes were promising and the study confirmed the feasibility and acceptability of RUFIT-NZ, the program (with some adaptations) is currently being evaluated in a full-scale RCT.…”
Section: Rufit-nz-deliveries To Men Through Professional Rugby Clubs mentioning
confidence: 79%
See 2 more Smart Citations
“…A −2.5 kg (95% CI −5.4 to 0.4) mean weight loss at 12 weeks favored the intervention group, who also showed positive improvements in waist circumference, resting heart rate, diastolic blood pressure, cardiovascular fitness and 'adherence' to lifestyle behaviors. All men who were followed up reported that they liked the program and would recommend it to other men [60]. As outcomes were promising and the study confirmed the feasibility and acceptability of RUFIT-NZ, the program (with some adaptations) is currently being evaluated in a full-scale RCT.…”
Section: Rufit-nz-deliveries To Men Through Professional Rugby Clubs mentioning
confidence: 79%
“…In 2015, a team led from New Zealand (NZ) obtained funding from the NZ Health Research Council and University of Otago to adapt and pilot FFIT for delivery as the Rugby Fans in Training NZ (RUFIT-NZ) in professional rugby clubs in Auckland and Dunedin. This reflected the fact that "Rugby (Union and League) is an integral part of NZ culture, the most popular spectator team sport, with high participation rates, particularly in Maori and Pacific peoples" [60] (p. 3 of 14). The NZ team were "cognizant that changes to the program may be needed to align with the rugby environment and cultural needs of men in NZ.…”
Section: Rufit-nz-deliveries To Men Through Professional Rugby Clubs mentioning
confidence: 99%
See 1 more Smart Citation
“…The FFIT concept has spread across the world via rugby (RUFIT-NZ, New Zealand) [20], football (Aussie-FIT, Australia) [21] hockey (Hockey FIT, Canada) [18] [19] and in Europe via EuroFIT [23]. Thus, this type of intervention needs refinement to fit into different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, the rugby clubs play an important role and Rugby Fans in Training New Zealand (RUFIT-NZ) delivered via professional rugby clubs demonstrated positive effects on weight and physiologic outcomes, as well as adherence to lifestyle behaviors [20]. Aussie-FIT, the first study in Australia to test an intervention targeting fan health delivered in Australian Football League settings, with 120 overweight/obese men, was carried out in 2018 [21].…”
Section: Introductionmentioning
confidence: 99%